2023
DOI: 10.1002/anie.202302111
|View full text |Cite
|
Sign up to set email alerts
|

Photochromic Polyoxoniobates with Photoinduced “D‐f‐A” Electron Transfer Mechanism

Abstract: Compounds with redox activities have appealing applications in catalytic, electronic and magnetic properties, but the redox inert of polyoxoniobates (PONbs) significantly limits their applications for a long time. In this work, we are able to integrate organophosphate and lanthanide cluster into PONb to create the first family of inorganic-organic hybrid organophosphate-Ln-PONb composite clusters. These novel species not only present the first family of redox active PONbs that can be reduced to form long-lived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…It was found that the S 0 –S 4 transition is the most prominent excitation at the band edge. By comparing the experimental spectra with the simulated spectra, we can conclude that the absorption at the band edge is mainly attributed to charge transfer transitions from cuprous iodide to pyridine. According to theoretical calculations, our experimental studies, and similarly reported studies, a plausible mechanism is proposed to account for the detection mechanism of CuI-TPPA . When CuI-TPPA is irradiated by X-ray, the charge carriers are excited.…”
Section: Resultssupporting
confidence: 63%
“…It was found that the S 0 –S 4 transition is the most prominent excitation at the band edge. By comparing the experimental spectra with the simulated spectra, we can conclude that the absorption at the band edge is mainly attributed to charge transfer transitions from cuprous iodide to pyridine. According to theoretical calculations, our experimental studies, and similarly reported studies, a plausible mechanism is proposed to account for the detection mechanism of CuI-TPPA . When CuI-TPPA is irradiated by X-ray, the charge carriers are excited.…”
Section: Resultssupporting
confidence: 63%
“…As a new kind of intelligent material, photochromic materials have important applications in the fields of information encryption, optical information storage, photoelectric materials, optical switches, and optical devices . Electron-deficient viologen derivatives (1,1′-disubstituted 4,4′-bipyridiniums), as good photochromic materials, are widely used in ink-free erasable printing, UV detection, and other fields. It is because of its electron-deficient nature that it can form charge transfer complexes with electron-rich species and has the redox capability of reversible electron transfer under the stimulation of an external environment, such as light. Therefore, the combination of viologen and multielectron species can construct more color-changing materials with excellent properties.…”
Section: Introductionmentioning
confidence: 99%
“…The O 1s core-level spectrum can be fitted to one major peak at 529.0 eV, and two weak peaks at 530.5 and 534.3 eV. After heating, there is a small 0.5 eV shift to lower binding energy at the peak of 530.5 eV position (Figure e,f), indicating that the O atoms in PONb serve as electron donors . As for N 1s, its core-level spectrum contains one major peak at 399.3 eV.…”
Section: Results and Discussionmentioning
confidence: 99%